Pentahelix as a Development Strategy for Opak Apik Singkong Business in Aek Bamban from an Islamic Economic Perspective - Kurnia Sandi Panjaitan; Zuhrinal M Nawawi; Marliyah Marliyah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
Aek Bamban is an area with significant potential for agro-industrial business development, particularly the Opak Apik cassava business. However, key challenges include a lack of innovation in business management, limited market access, and weak synergy among local stakeholders. This study aims to analyze the implementation of the Pentahelix strategy as a solution for developing the Opak Apik cassava business from an Islamic economic perspective. The Pentahelix model involves five critical elements: government, academia, business, community, and media, working together to create a collaborative ecosystem that fosters business growth. This qualitative study employs the SOAR method, using the O-A approach, which focuses on aspirations and opportunities to drive sustainable and competitive business strategies. The O-A approach identifies existing opportunities and long-term aspirations to create sustainable and competitive businesses. From an Islamic economic perspective, principles such as tauhid (monotheism), nubuwah (prophethood), khilafah (stewardship), adl (justice), and ma'ad (the afterlife) are integrated into every aspect of business development. The findings show that the Pentahelix collaboration and the O-A strategy can expand market access, enhance product innovation, and promote socio-economic balance based on Islamic values. This strategy not only fosters economic growth but also contributes to societal welfare through justice and sustainability